Legal Regime as the Basis of Division of Land Into Categories - Ekaterina Nikolaevna Malanina (Сибирское юридическое обозрение, 2011)
The author of this article analyzes one of the basic concepts of Russian law of land - the legal regime of land. However, despite unconditional importance of the specified concept, today in the theory of law of land no definition of this concept is provided. This article examines different interpretations of the concept «legal regime of land» provided by Russian law scholars and practitioners. That allows for understanding specific features of legal regime of land used for different purposes.